Arsenic behavior during gallic acid-induced redox transformation of jarosite under acidic conditions. (September 2020) - Tang, Yuanjun; Xie, Yingying; Lu, Guining; Ye, Han; Dang, Zhi; Wen, Zining; Tao, Xueqin; Xie, Chunsheng; Yi, Xiaoyun
Abstract: Jarosite is an important scavenger for arsenic (As) due to its strong adsorption capacity and ability to co-precipitate metal(loid)s in acid mine drainage (AMD) environments. When subjected to natural organic matter (NOM), metastable jarosite may undergo dissolution and transformation, affecting the mobility behavior of As. Therefore, the present study systematically explored the dissolution and transformation of jarosite, and the consequent redistribution of coprecipitated As(V) under anoxic condition in the presence of a common phenolic acid–gallic acid (GA). The results suggested that As(V) incorporating into the jarosite structure stabilized the mineral and inhibited the dissolution process. Jarosite persisted as the dominant mineral phase at pH 2.5 up to 60 d, though a large amount of structural Fe(III) was reduced by GA. However, at pH 5.5, jarosite mainly transformed to ferrohexahydrite (FeSO4 ·6H2 O) with GA addition, while the principal end-product was goethite in GA-free system. The dissolution process enhanced As(V) mobilization into aqueous and surface-complexed phase at pH 2.5, while co-precipitated fraction of As(V) remained dominant under pH 5.5 condition. Result of XPS indicated that no reduction of As(V) occurred during the interaction between GA and As(V)-bearing jarosite, which would limit the toxicity to the environment. The reductive process involved that GA promoted the dissolution of jarosite via the synergistic effect of ligand and reduction, following by GA and release As(V) competing for active sites on mineral surface. The findings demonstrated that phenolic groups in NOM can exert great influence on the stability of jarosite and partitioning behavior of As(V). Graphical abstract: Image 1 Highlights: GA promoted dissolution of jarosite via synergistic effect of ligand and reduction. GA enhanced As(V) mobility mainly by competition for active sites on mineral surface. Coprecipitated As(V) inhibited the abiotic GA-induced transformation of jarosite. Jarosite transformed to ferrohexahydrite at pH 5.5 with GA addition.